STUDI DESKRIPTIF TENTANG FAKTOR YANG MEMPENGARUHI PENYALAHGUNAAN NAPZA PADA KALANGAN REMAJA DI DESA PAKUSARI KABUPATEN JEMBER - Eka Fitriyawati Ladjiru; Marwah (Jurnal Kesehatan dr. Soebandi, 2016)
Drug Abuse (Psychotropic Narcotics and Addictive Substances) in adolescents in Sumber Agung Village always has an increase every year, there are a number of things behind this abuse namely low levels of education, lack of knowledge, and peer influence. According to the Jember Narcotics Agency that the number of drug abuse in 2011 to 2012 the age category of 18-25 years is as many as 28 people and the prevalence continues to increase every year.The purpose of this study is to describe the factors of knowledge, family factors and peer factors that influence drug abuse among adolescents in Pakusari Village, Jember Regency.The research design used is descriptive approach. The population in this study were 30 respondents. The sample in this study was taken in total sampling with a sample of 30 teenagers. The research instrument was carried out by giving questionnaires to adolescents to describe the factors that influence drug abuse. The results of this study were analyzed using Frequency Distribution. The results of the Frequency Distribution Test indicate that the first factor influencing drug abuse among adolescents is the knowledge factor of adolescents (25.8%) good, knowledgeable (45.2%) sufficient and knowledgeable (25.8%) lacking. The second factor affecting drug abuse among adolescents is the family factor in adolescents (42.2%) yes and (51.6%) no. The third factor influencing drug abuse among adolescents is the peer factor in adolescents (80%) yes and (20%) no. So it can be concluded that the majority of adolescents who influence drug abuse are knowledgeable, lack of family factors and the presence of peers